The Effect of Sustainability Report Disclosure, Firm Size, and Liquidity on Firm Value: Evidence from Indonesian Mining Companies - Iriana Auliyah Auliyah; Jesicha Ardhyana Destriani; Mursalam Salim; Septyana Prasetianingrum; Entar Sutisman (The Es Accounting And Finance, 2026)
This study examines whether sustainability report disclosure, firm size, and liquidity affect firm value in Indonesian mining companies. Mining firms operate in a capital-intensive and environmentally sensitive sector; therefore, investor valuation may be shaped not only by financial indicators but also by sustainability transparency. The study applies a quantitative explanatory design using secondary data from mining-sector companies listed on the Indonesia Stock Exchange during 2020–2024. From a population of 39 firms, 14 companies were selected through purposive sampling, generating 70 firm-year observations. Firm value was measured using Price to Book Value, sustainability report disclosure was measured through a disclosure index, firm size used the natural logarithm of total assets, and liquidity used the current ratio. Multiple linear regression with SPSS 22 was employed after classical assumption testing. The results show that sustainability report disclosure has a negative and significant effect on firm value, with a coefficient of −73.065 and significance of 0.000. Firm size has a positive and significant effect, with a coefficient of 3.000 and significance of 0.000. Liquidity has a positive but insignificant coefficient of 0.874 and significance of 0.344. The model explains 42.5% of firm-value variation. These findings imply that sustainability disclosure in mining firms may be interpreted as a costly or risk-revealing signal unless supported by credible sustainability performance, while company scale remains a strong valuation signal.